Energy absorption characteristics and a meta-model of miniature frusta under axial impact. Issue 3 (3rd May 2016) - Azimi, Mohammadbagher B.; Asgari, Masoud
ABSTRACT: In this paper, crushing characteristics of small-sized conical tubes called miniature frusta under axial loading have been studied. Finite-element model is developed using non-linear explicit code LS_DYNA to investigate the non-symmetrical fold patterns as well as material and geometrical non-linearity of frusta. Numerical simulation is first validated by confirming the results using experimental test data. Effects of shell thickness, semi-epical angle of cone and frusta's length on energy absorption characteristics are then studied by carrying out a parametric study. Based on the crushing parameters of numerous examples, a simplified analytical model as a meta-model for the mean crushing force of miniature frusta is presented using a Genetic Algorithm optimization for finding the meta-model coefficients. Miniature frusta show promising behaviour in lightweight design and crash analysis as their response results in low peak force and efficient-specific energy absorption. Obtained results from the developed meta-model showed good concurrence with finite elements method (FEM) model.